1981
DOI: 10.1007/bf01249131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cholecystokinin octapeptide sulfate ester on brain monoamine metabolism in rats

Abstract: The effects of intracerebroventricular administration of an 80 pmole dose of cholecystokinin octapeptide sulfate ester (CCK-8-SE) were tested on the dopamine (DA), norepinephrine (NE) and serotonin (5-HT) turnovers of the hypothalamus, mesencephalon, amygdala, septum, striatum and cerebral cortex in rats. CCK-8-SE in an 80 pmole dose decreased the DA turnovers of the hypothalamus, mesencephalon, amygdala and septum, while it increased that of the striatum. The NE turnovers were increased in the hypothalamus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The i.c.v, injection of CCK has been reported to have little influence on the serotonin content in the brain (Fekete et al, 1981;Mashal and Hunt, 1983), although some CCK-8 immunoactive neurons in the medulla oblongata contain serotonin (Mantyh et al, 1984). Although the effects of CCK-8 on monoamines have been well investigated (Fekete etal., 1981), there are few reports about the change in CCK-8 level caused by serotonin depletion.…”
Section: Discussionmentioning
confidence: 97%
“…The i.c.v, injection of CCK has been reported to have little influence on the serotonin content in the brain (Fekete et al, 1981;Mashal and Hunt, 1983), although some CCK-8 immunoactive neurons in the medulla oblongata contain serotonin (Mantyh et al, 1984). Although the effects of CCK-8 on monoamines have been well investigated (Fekete etal., 1981), there are few reports about the change in CCK-8 level caused by serotonin depletion.…”
Section: Discussionmentioning
confidence: 97%
“…These data strongly suggest that the peptide has no direct action on the pitu itary and probably acts at the hypothalamic level. Indeed, the modifications in mono amine (decrease in dopamine and serotonin and increase in norepinephrine) turnover, observed in the hypothalamus of rats treated with CCK-8 [11], can account for the hor monal changes observed in the present inves tigation. Moreover, recently the coexistence of dopamine and a CCK-like peptide in brain neurons has been demonstrated [39].…”
Section: Discussionmentioning
confidence: 70%
“…First, if it is admitted that DA neurons, i.e., those which possibly terminate in the MPO, stimulate LHRH neurons to secrete LHRH, either directly or indi rectly, CCK-8-S will exert a certain stimulatory effect on this DA action. It was shown that intraventricular adminis tration of CCK-8-S increased DA turnover in the striatum, although it decreased the turnover in other areas [8]. In the substantia nigra and ventral tegmental area, CCK excited the electrical activity of the DA cell [25].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of investigations have found pharmacological [7,8], electrophysiological [25] and bio chemical [18] interactions between CCK and DA systems.…”
Section: Introductionmentioning
confidence: 99%